Employee performance among female employees during working from home period of pandemic Covid19 movement control order (MCO) in Selangor - Nurul Syifa, Roslan (2022)
The purpose of this study is to examine employee performance among female employees while working from home during the Covid19 pandemic Movement Control Order (MCO) in Selangor. It is postulated that this working arrangement influences employee performance. The questionnaire was distributed online and collected back from the target respondents. Qualified raw data collected was analysed using the Statistical Package for Social Science (SPSS) Version 26th. The results indicated that only work hour is significant to employee performance with weak relationship. Workload, role conflict and family responsibilities is not related to employee performance.